"Reclaiming Control" Patient Acceptance and Adherence to HIV Post-Exposure Prophylaxis Following Sexual Assault. (14th September 2021) - Draughon Moret, Jessica E.; Sheridan, Daniel J.; Wenzel, Jennifer A.
Sexual assault is an irrefutable trauma; an insult to the autonomy of the person forced into sexual acts. Sexual assault sequelae range from physical injury and acute traumatic stress, to pregnancy and sexually transmitted infections, including human immunodeficiency virus (HIV). HIV post-exposure prophylaxis (HIV PEP) following sexual assault may decrease the likelihood of HIV transmission. Many patients seeking healthcare post-sexual assault either do not initiate HIV PEP or do not complete the 28-day medication regimen. In this qualitative interpretive description, we interviewed sexual assault patients ( N =11) about HIV PEP discussions/reactions, attitudes and understanding related to HIV and PEP, and barriers and facilitators of HIV PEP acceptance and adherence. Participants described a process of losing and reclaiming control throughout post-assault care and follow-up; and how this affected HIV PEP-related decision-making. Most HIV PEP decisions were described as a process of reclaiming control over one outcome while simultaneously losing control of another.